Brain plasticity associated with prolonged shooting training: a multimodal neuroimaging investigation from a cross-sectional study - Zhang, Keying; Zhao, Tao; Ding, Yu; Cheng, Jia; Cao, Chunmei (Frontiers in Human Neuroscience, 2025)
BackgroundAlthough training has been recognized as a potential contributor to neuroplasticity in athletes, the impact of prolonged shooting training on human brain plasticity remains unclear in the existing literature.MethodsIn this cross-sectional study, we used a multimodal neuroimaging analysis, including the analysis of functional blood oxygenation level-dependent (BOLD) magnetic resonance imaging (MRI) images, structural T1-weighted MRI images, and diffusion MRI images, to systematically identify differences between elite shooters and normal controls.ResultsThe results showed that compared to male normal controls, male elite shooters had higher regional homogeneity (ReHo) in the frontal lobe, parietal lobe, precuneus, thalamus, and cingulate gyrus, as well as higher functional connectivity between the medial frontal cortex (MedFC) and temporooccipital middle temporal gyrus (toMTG). Male elite shooters also showed higher cortical thickness in the right inferior temporal lobe; lower fractional anisotropy (FA) values in the right superior longitudinal fasciculus (SLF), right inferior fronto-occipital fasciculus (IFF), and right anterior thalamic radiation (ATR); lower axial diffusivity (AD) value in forceps minor and left ATR; and lower structural connectivity between right putamen and right inferior parietal cortex (IPC), right IPC and right paracentral cortex, and right paracentral cortex and right superior parietal cortex (SPC).ConclusionElite male shooters exhibited optimized resting-state functional activity, functional connectivity, and morphological features compared to normal controls. Prolonged shooting training may contribute to enhancing the brain’s functional and structural plasticity related to motor control, attentional focus, and emotion regulation in male shooters; however, similar changes have not been observed in female shooters.